EPISTEMOLOGICAL STUDY OF ORNAMENTAL FISH COLOR ENHANCEMENT THROUGH FEEDING - Dewi Astuti Sartikasari; Junianto Junianto (Universitas Mataram, 2025)
Ornamental fish are fish that have an attractive appearance. The attractiveness of ornamental fish can be seen from the brilliant color, physical shape and completeness, behavior, and health of the fish. Feeding is one of the factors that can provide brightness to ornamental fish. The aim of this research is to conduct an epistemological study of increasing the color of ornamental fish through feeding. The method used in this research is literature review analysis. The addition of color-brightening factors or nutrients can come from chemicals and non-chemical or natural ingredients, it is recommended to use natural ingredients. The results concluded that providing color-brightening factors or nutrients in fish food with the right dosage and feeding can cause the brightness of the fish's color to increase.